Influence of tree species on understory vegetation diversity and mechanisms involved—A critical review for temperate and boreal forests - Barbier, Stéphane; Gosselin, Frédéric; Balandier, Philippe (Forest ecology and management, 2008)
Tree species composition is a primary attribute of forest ecosystems, and is often manipulated by silvicultural practices. Forest management to diversify tree species is now being promoted to favor biodiversity. To assess the soundness of this policy we reviewed and analyzed the literature on the relationship between tree species composition and floristic diversity, including the mechanisms involved therein. Coniferous forests generally provide less diversified vascular understories than broadleaved forests. At the tree species scale, there are not enough reports to draw firm conclusions on the effect of any particular species. Mixing of deciduous and coniferous tree species generally affects understory diversity, but in almost all cases maximum diversity is observed in one of the pure stands, not in mixed stands. Understory vegetation is influenced by overstory composition and structure through modifications of resource availability (light, water and soil nutrients) and other effects, such as physical characteristics of the litter layer. Overstory light transmittance and diverse properties of forest litter are factors that have been most fully studied to date, but other factors such as throughfall water quantity and chemistry may also play a role. While the relative importance of mechanisms that account for the effect of overstory on understory biodiversity has often been discussed, these mechanisms have rarely been the subject of formal experiments. Overall, varying management practices and site attributes make it difficult to generalize results. They combine with the effects of tree species in influencing understory vegetation diversity, but they have been rarely considered. Future research is needed to gain a better understanding of the relationship between overstory and understory diversity and establish general laws.